What is the best way to share an HIV diagnosis with an intimate partner? An experimental study of assertive disclosure communication. Issue 9 (1st September 2020) - Evangeli, Michael; Collins, Jodie
ABSTRACT: Living with HIV presents challenges to wellbeing and managing one's own and others' health. Sharing an HIV positive diagnosis can increase social support and antiretroviral adherence and reduce onward HIV transmission. However, HIV disclosure anxiety is common with concerns about partner responses. There is limited research on whether the way HIV is shared affects partners' responses. We assessed whether communication style influences hypothetical partner responses in intimate relationships. Two hundred and four participants (83% female; median age 20, IQR 19-23) were shown four vignettes (high assertion regular partner, low assertion regular partner, high assertion casual partner, low assertion casual partner). Participants responded as the intimate partner to questions addressing affective and cognitive reactions to HIV diagnosis sharing. Assertive compared to non-assertive communication led to intimate partner responses with lower negative affect, warmer feelings toward the character and greater intentions to provide support and to continue a sexual relationship. Participants responded with more global negative affect and shock, and greater intention to provide support and to continue a sexual relationship if the character was a regular compared to a causal partner. Future work could explore whether people with HIV should be assisted to share their diagnosis assertively for greater benefits.